PENGGUNAAN METODE SOROGAN DALAM MENINGKATKAN KUALITAS BACAAN AL-QUR’AN - Afif Nurseha (Jurnal Keislaman, 2022)
This research is motivated by the importance of improving the quality of reading the Qur'an to students, as a step to anticipate the decline of the Qur'anic generation that is currently happening. Islamic boarding schools apply the use of the sorogan method in Islamic boarding schools, designed to form Qur'anic people who believe in the truth of the contents of the Qur'an, read, memorize, and understand the meaning contained properly and correctly. This requires to form individuals who are proficient in reading the Qur'an in accordance with the science of tajwid, makhorijul letters, shifatul letters and try to produce tartil reading quality. The use of the sorogan method is unique and different from the others, so that triggers are interested in research. The purpose of the study was to examine how the use of the sorogan method in improving the quality of reading the Qur'an at the Al-Istiqomah Tanjungsiang Islamic boarding school. This research was conducted with a descriptive qualitative research method with a case approach. The research subjects used were the leadership of the Islamic boarding school, the community council (teacher) of the students of the Al-Istiqomah Tanjungsiang Islamic boarding school. The instruments used are interviews and observations. Meanwhile, data reduction, data presentation, and data verification were used as steps to analyze the data. The results of this study, namely the use of the sorogan method in improving the quality of reading the Qur'an at the Al-Istiqomah Tanjungsiang Islamic boarding school applied, namely (a). get used to using the sorogan method in improving the quality of reading the Qur'an as it is done at dawn, ba'da magrib and taqroruddurus time (b). knowing the advantages of the sorogan method, seen by looking at the results of using the sorogan method then students practicing and developing it (c). before using the sorogan method, it was rather difficult for students to read the Qur'an (d). get used to discipline by coming to the Koran not too late (e) getting used to using the sorogan method, namely reading Al-Fatihah letters together, reading prayers, students facing the ustadz one by one, and finally closing prayers together. same. As for the use of the sorogan method, it can improve the quality of reading the Qur'an, as there are some students who win in the field of tahfidz and qiro'at.